2011
DOI: 10.1007/s10800-011-0261-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification effects of [Li,La]TiO3 on the electrochemical performance of Li[Ni0.35Co0.3Mn0.35]O2 cathode material for lithium–ion batteries

Abstract: Surface modification of Li[Ni 0.35 Co 0.3 Mn 0.35 ] O 2 as a cathode material of lithium-ion batteries was carried out by hydrothermal treatment using lithium lanthanum titanate ([Li,La]TiO 3 ). The modified surfaces were analyzed by morphology observation using transmission electron microscopy and by element investigation using X-ray photoelectron spectroscopy. It was thereupon found that the [Li,La]TiO 3 -coated layer formed by the surface modification played a definitive role in suppressing the solid electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…To solve these issues, some strategies (such as surface modification and ion doping) have been employed to improve NCM523 . Metal oxides (such as Al 2 O 3 , ZnO, and TiO 2 ), fluorides (such as LiF and AlF 3 ), and phosphates are commonly used as coating materials to protect the electrode material by preventing it from contacting electrolyte . Furthermore, to obtain better lithium‐ion conductivity, superionic conductors were explored as the coating materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve these issues, some strategies (such as surface modification and ion doping) have been employed to improve NCM523 . Metal oxides (such as Al 2 O 3 , ZnO, and TiO 2 ), fluorides (such as LiF and AlF 3 ), and phosphates are commonly used as coating materials to protect the electrode material by preventing it from contacting electrolyte . Furthermore, to obtain better lithium‐ion conductivity, superionic conductors were explored as the coating materials .…”
Section: Introductionmentioning
confidence: 99%
“…14 Metal oxides [15][16][17] (such as Al 2 O 3 , ZnO, and TiO 2 ), fluorides 18,19 (such as LiF and AlF 3 ), and phosphates 20 are commonly used as coating materials to protect the electrode material by preventing it from contacting electrolyte. 21,22 Furthermore, to obtain better lithium-ion conductivity, superionic conductors were explored as the coating materials. 23,24 One of the most common lithium superionic conductors is lithium boron oxide, Li 2 O-2B 2 O 3 (LBO).…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion conductors are also broadly applied as coating materials for cathode surfaces, which mainly contain LiF, LiTaO 3 , Li 2 ZrO 3 , Li 2 SiO 3 , Li 2 SnO 3 , Li 2 TiO 3 , Li 3 VO 4 , LiAlO 2 , LiLaTiO 3 , Li 3 PO 4 , NaTi 2 (PO 4 ) 3 , LiBO 2 , LiFeO 4 and Li 3 Fe 2 (PO 4 ) 3 . , Li et al reported a uniform and dense lithium conductive LiTaO 3 layer with controllable layer thicknesses coated on the NMC by ALD. The inactive coated materials often demonstrate reduced ionic conductivity, as well as hindered lithium ion transport into and out of the electrode particles, resulting in limited performance improvement.…”
Section: Modificationsmentioning
confidence: 99%